To compare the intended brand identity and the perceived brand image of the City Of Johannesburg (CoJ) brand by conducting a comparative thematic content analysis between CoJ's official website as well as a select group of Johannesburg residents - Mabaso, Mathapelo (The IIE, 2017)
This study is a cross-sectional exploratory case study, focusing on comparing the intended brand identity and the perceived brand image of the City of Johannesburg (CoJ) brand by conducting a comparative thematic content analysis between COJs official website as well as a select group of Johannesburg residents. The study attempts to establish if there is a difference between the brand identity that CoJ projects on its website and how the brand is perceived by residents. This paper moves from the point of view that cities offer several advantages to the concentration of economic activities and as such, municipalities like CoJ have the mammoth task of building a strong municipality brand that can help boost its economic growth, tourism, investment and attract new resident. CoJ should use their brands to tell a story and why they should be the first choice whether be it for tourism, investment, residency etc. In telling this story, COJ must ensure that their intended brand identity matches their brand image as experienced and perceived by their residents so as to achieve the above. Research has been done around brand identity and brand image and there seems to be an understanding that brand identity and brand image are intertwined (Konecnik and Go, 2007) and therefore the study will move from the point of view that brand identity and brand image are parallel to each other. CoJ needs to make sure that their brand identity is well communicated and is consistent on all their platforms as well as in their messaging to ensure that there is no gap between the two. By aligning brand identity with the perceived and experience brand image, CoJ can claim to be a credible and trusted brand by its residents. The concepts brand, brand identity and brand image mean different things to different people, their meanings are explored in section 5 of this paper, as well as in the literature review, section 6 in more depth. The link between brand identity and brand image is also explored in the literature review.
Keywords: Brand Identity; Brand Image; Brand; Economic Growth; Tourism